2021
DOI: 10.1001/jamanetworkopen.2021.7470
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Costs of Low-Value Preoperative Testing for Cataract Surgery Within the Veterans Health Administration

Abstract: Key Points Question To what extent are low-value preoperative tests used before cataract surgery in the US Veterans Health Administration, and what is the variability and cost of these tests? Findings In this cohort study including 69 070 cataract procedures performed among 50 106 patients, almost half were preceded by at least 1 low-value test. Compared with low-complexity facilities, higher facility-level complexity was associated with higher odds of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…7 Prior investigations on the value of various preoperative testing strategies have often centered around low-risk surgery, like cataract surgery, demonstrating an absence of a morbidity and mortality benefit while incurring a marked cost to the healthcare system. 10 Although elective EVAR and open AAA repair are higher-risk surgeries than cataract surgery, the current study suggests that there are areas for value analysis surrounding preoperative stress tests prior to aortic surgery to limit costs but still providing high-quality vascular surgical care. Further studies to better delineate which patients should undergo preoperative stress testing to maximize benefit and minimize financial implications are indicated.…”
mentioning
confidence: 88%
“…7 Prior investigations on the value of various preoperative testing strategies have often centered around low-risk surgery, like cataract surgery, demonstrating an absence of a morbidity and mortality benefit while incurring a marked cost to the healthcare system. 10 Although elective EVAR and open AAA repair are higher-risk surgeries than cataract surgery, the current study suggests that there are areas for value analysis surrounding preoperative stress tests prior to aortic surgery to limit costs but still providing high-quality vascular surgical care. Further studies to better delineate which patients should undergo preoperative stress testing to maximize benefit and minimize financial implications are indicated.…”
mentioning
confidence: 88%
“…We previously found that 47.0% of generally healthy patients (ASA-PS I or II) undergoing a carpal tunnel release in the Veterans Health Administration (VA), the largest integrated healthcare system in the USA, had at least one low-value preoperative screening test within 30 days before surgery (Harris et al 2019). We also found that 49% of 50,106 cataract surgeries performed in VA in 2017 were preceded by one or more preoperative screening test with an overall annual cost of $2.6 million (Mudumbai et al 2021). In each of these studies, substantial variability existed between facilities, with some ordering almost zero tests and others routinely ordering tests for almost all patients undergoing these procedures.…”
Section: Introductionmentioning
confidence: 93%
“…3,5,13,14 LVC in the preoperative setting has many gaps: there is a few studies with the types of services and/or care beyond preoperative exams that do not add value; it is unknown whether this care positively or negatively impacts clinical outcomes in patients with intermediate or high-risk surgery; the scientific evidence at this moment is not comprehensive enough for LVC in this field and this problem has seen only moderate improvements over the last few decades. 10,[13][14][15][16][17][18][19] Given this knowledge gap, a deeper understanding of how conceptual studies defined and described the consequences setting associated with LVC in preoperative of low-risk surgeries can be the first step to discuss this topic from different points of view and promote high-value care. 10,20 This scoping review seeks to identify and summarise LVC in low-risk surgeries definitions and to propose a framework with the potential consequences this care.…”
Section: Introductionmentioning
confidence: 99%
“…This period is complex and presents a variety of situations and interpretations that may or may not be considered LVC and that need to be detailed 3,5,13,14 . LVC in the preoperative setting has many gaps: there is a few studies with the types of services and/or care beyond preoperative exams that do not add value; it is unknown whether this care positively or negatively impacts clinical outcomes in patients with intermediate or high‐risk surgery; the scientific evidence at this moment is not comprehensive enough for LVC in this field and this problem has seen only moderate improvements over the last few decades 10,13‐19 …”
Section: Introductionmentioning
confidence: 99%